How do auditory verbal hallucinations in patients differ from those in non-patients? - Larøi, Frank (Frontiers in Human Neuroscience, 2012)
Auditory verbal hallucinations (AVHs) are experienced by individuals with various clinical diagnoses, such as psychosis, but also a significant minority of healthy individuals from the general population may experience them. Although much research has been carried out the past few decades, the mechanisms and factors underlying the emergence of AVHs is still poorly understood. One way of clarifying this issue involves comparing AVHs in patient and nonpatient populations. In particular, differences between these groups will provide important information concerning the emergence of AVHs. After a general presentation and discussion of the notion of a continuum hypothesis, studies comparing patients with nonpatients experiencing AVHs will be reviewed. This will comprise studies examining the phenomenological characteristics of AVHs in addition to neuroimaging and cognitive studies. Although we are beginning to elucidate important differences on a phenomenological level between these two types of AVHs, far too few studies have directly compared patient and nonpatient AVHs in terms of underlying cerebral correlates and cognitive mechanisms. Nevertheless, and based on recent research on phenomenological differences, two issues stand out that need to be addressed, namely, the highly negative emotional content of AVHs in patients and the early onset of AVHs in nonpatients populations. Suggestions for future research will be discussed.